Persepsi Masyarakat Sedayu Desa Kediri Lombok Barat Terhadap Praktik Murabahah di Koperasi Ponpes Nurul Hakim - Hirjan, Muhammad; Ariadi Muslim, Muh; Hadiyani, Baiq; Febrian, Dodi (TAFAQQUH, 2024)
This research aims to understand the perception of the Murabahah practice carried out by the Ponpes Nurul Hakim cooperative in implementing the Murabahah product system in Kediri Village, West Lombok. This study is a field research using qualitative case study data. In data collection, the author used interviews as a guideline with the director and employees of the Ponpes Nurul Hakim Kediri cooperative, as well as with members and the community of the Ponpes Nurul Hakim cooperative. Meanwhile, documentation was carried out by recording or obtaining data from the Ponpes Nurul Hakim cooperative, such as the history of the Ponpes Nurul Hakim cooperative, organizational structure, and financing illustrations at the Ponpes Nurul Hakim cooperative. The results of this study indicate that the perception of the Sedayu community in Kediri Village, West Lombok, towards the Murabahah practice at the Ponpes Nurul Hakim cooperative is categorized into several groups. The first group consists of those with a positive perception. The second group consists of those with a negative perception. The findings show that the community's perception of the Murabahah product in the cooperative is to avoid the interest system, with a percentage of 85.45%. Meanwhile, 13.635% expressed disagreement or negative perceptions due to a lack of community interest and understanding of the regulations and operational implementation of the Murabahah product system, caused by insufficient socialization and community curiosity.